2011
DOI: 10.1177/0748730411414170
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-Specific Mutation of Clock Alters the Quantitative Measurements of Physical Activities without Changing Behavioral Circadian Rhythms

Abstract: Even though peripheral circadian oscillators in the cardiovascular system are known to exist, the daily rhythms of the cardiovascular system are mainly attributed to autonomic or hormonal inputs under the control of the central oscillator, the suprachiasmatic nucleus (SCN). In order to examine the role of peripheral oscillators in the cardiovascular system, we used a transgenic mouse where the Clock gene is specifically disrupted in cardiomyocytes. In this cardiomyocyte-specific CLOCK mutant (CCM) mouse model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…, the p85α subunit of PI3K). We have previously reported that the phosphorylation status of two kinases that are downstream of PI3K (namely AKT and GSK3β) appear to be under circadian clock control (as evidenced by loss of time-of-dependent oscillations in CCM hearts) (Durgan et al 2010; Ko, et al 2011); similar findings regarding clock regulation of AKT phosphorylation have been reported in extra cardiac tissues, using germline Bmal1 null and Per2 mutant mice (Anea, et al 2009; Carvas, et al 2012). Consistent with impaired PI3K activity, both AKT and GSK3β phosphorylation were attenuated in CBK hearts (Figure 4E).…”
Section: Discussionsupporting
confidence: 65%
“…, the p85α subunit of PI3K). We have previously reported that the phosphorylation status of two kinases that are downstream of PI3K (namely AKT and GSK3β) appear to be under circadian clock control (as evidenced by loss of time-of-dependent oscillations in CCM hearts) (Durgan et al 2010; Ko, et al 2011); similar findings regarding clock regulation of AKT phosphorylation have been reported in extra cardiac tissues, using germline Bmal1 null and Per2 mutant mice (Anea, et al 2009; Carvas, et al 2012). Consistent with impaired PI3K activity, both AKT and GSK3β phosphorylation were attenuated in CBK hearts (Figure 4E).…”
Section: Discussionsupporting
confidence: 65%
“…After the feeding regimen mPer2 Luc mice were subjected to the same assays used for C57BL/6J mice. Additionally, both HFD-fed and LFD-fed mPer2 Luc mice were subjected to examination of wheel-running locomotor activity rhythms as previously described (40). Some age-matched female mPer2…”
Section: Methodsmentioning
confidence: 99%
“…For both cell types, the medium was changed ϳ24 h after plating so as to reduce the FBS concentration to 5%, and about 12 h later cultures were exposed to medium containing 50% adult horse serum for 2 h. Thereafter, serum-shocked SVC and BMDM were maintained in serumfree recording medium containing 0.1 mM beetle luciferin (Promega), 25 units/ml penicillin, and 25 g/ml streptomycin for bioluminescence analysis as described previously (40). Individual cultures were sealed airtight with sterile glass coverslips (VWR) and sterile silicon grease (Dow Corning).…”
Section: Methodsmentioning
confidence: 99%
“…Time-of day dependent oscillations have been reported in the heart for the voltage dependent potassium channels K v 1.5 and K v 4.2 158 , and the L-type voltage-gated calcium channel subunit VGCCα1D. 159 Also, L-type calcium channel current densities increase during the active period which is consistent with the nocturnal elevation in murine heart rate. 155,157 Moreover, circadian variations in potassium channel interacting protein-2 (KChIP2) affect potassium channel opening in a manner that is consistent with changes in action potential duration and circadian variations in heart rate.…”
Section: Iii) Circadian Mechanism and Cardiac Electrophysiologymentioning
confidence: 60%